Daily spirometry in an acute exacerbation of adult cystic fibrosis patients. (August 2018) - Stephen, Michael J; Long, Alex; Bonsall, Chad; Hoag, Jeffrey B; Shah, Smita; Bisberg, Dorothy; Holsclaw, Douglas; Varlotta, Laurie; Fiel, Stan; Du, Doantrang; Zanni, Robert; Hadjiliadis, Denis
To help answer the question of length of intravenous antibiotics during an acute exacerbation of cystic fibrosis (CF), we had subjects to follow daily home spirometry while on intravenous antibiotics. CF patients, 18 and older, with an acute exacerbation requiring intravenous antibiotics had a daily FEV1. The average time to a 10% increase over their initial sick FEV1 was calculated, as well as the time to a new baseline. A total of 25 subjects completed the study. Ten of the 25 subjects did not have a sustainable 10% increase in FEV1. Of the 15 subjects with a sustainable 10% increase in FEV1, it took 5.2 days (±4.5) after day 1, while a new baseline was achieved on average at 6.6 days (±4.8) after day 1. Given the wide range of time to a 10% improvement and new baseline, it is recommended there should be flexibility in length of intravenous antibiotics in CF, not by a preset number.